Manajemen Public Relation Kementrian Pariwisata dan Ekonomi Kreatif dalam Menyediakan Informasi Publik Terkait Pariwisata - Muhammad Nur Arfan; Istisari Bulan Lageni (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Public relations management is a strategic approach employed by the Ministry of Tourism and Creative Economy (Kemenparekraf) in providing public information related to tourism. This study aims to analyze the public relations management process of Kemenparekraf in disseminating tourism-related public information by using a descriptive qualitative approach and the public relations management theory proposed by Cutlip, Center, and Broom. Research data were obtained through in-depth interviews, literature review, and observation. The results indicate that Kemenparekraf implements the four stages of public relations management comprehensively: defining public relations problems, planning and programming, taking action and communicating, and evaluating the program. Kemenparekraf utilizes various digital and conventional platforms to disseminate tourism information, with an emphasis on transparency, accuracy, and information accessibility. The implementation of the Public Information Disclosure Act is also a major focus, including the provision of information that must be periodically disclosed, immediately announced, and available at all times. Effective public relations management enables Kemenparekraf to address challenges in the dissemination of complex and dynamic tourism information and to ensure equitable access to tourism information for various stakeholders, thereby supporting sustainable tourism development in Indonesia.